2019
DOI: 10.1016/j.jad.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of first-line smoking cessation pharmacotherapies in bipolar disorders: Subgroup analysis of a randomized clinical trial

Abstract: Post hoc analyses of EAGLES data to examine safety and efficacy of first-line smoking cessation pharmacotherapies in smokers with bipolar disorders (BD). Methods: Smokers with BD I/II (n = 285; 81.4% with BD I) and a comparison nonpsychiatric cohort (NPC; n = 2794) were randomly assigned to varenicline, bupropion, nicotine replacement therapy (NRT), or placebo for 12 weeks, plus weekly counseling. Primary outcomes were occurrence of moderate to severe neuropsychiatric adverse events (NPSAEs) and Weeks 9-12 bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…In conclusion, prospective studies are necessary to confirm our results and to assess causality of our findings (e.g., metabolic syndrome and smoking status). Nevertheless, this study stresses the necessity to encourage smoking cessation for BD individuals, especially since recent randomized controlled trials demonstrated efficacy and security of therapies for smoking cessation in these patients 2,21,26 . Our findings suggest that quitting smoking may be more difficult for the most severe patients, but that patients with BD as a group are expected to benefit from quitting regarding their psychiatric and metabolic health.…”
Section: Discussionmentioning
confidence: 72%
“…In conclusion, prospective studies are necessary to confirm our results and to assess causality of our findings (e.g., metabolic syndrome and smoking status). Nevertheless, this study stresses the necessity to encourage smoking cessation for BD individuals, especially since recent randomized controlled trials demonstrated efficacy and security of therapies for smoking cessation in these patients 2,21,26 . Our findings suggest that quitting smoking may be more difficult for the most severe patients, but that patients with BD as a group are expected to benefit from quitting regarding their psychiatric and metabolic health.…”
Section: Discussionmentioning
confidence: 72%
“…A post-hoc analysis suggests a higher abstinence rate with varenicline compared to bupropion or NRT ( 79 ), but with all three pharmacological interventions (bupropion, varenicline, NRT) being, by large, equally effective for TUD or ND ( 80 ), safety comes to the fore. NRT has little contraindications or side effects, and can be considered in almost all people with TUD.…”
Section: Treatment Of Comorbid Bipolar Disorder and Tobacco Use Disordermentioning
confidence: 99%
“…17 Similarly, it has been reported that individuals with psychiatric disorders are prone to experience relapse of psychiatric symptoms. 18 19 Although many RCTs and post hoc analyses of some RCTs showed consistent results about varenicline safety in subjects with specific psychiatric disorder, [20][21][22][23][24][25][26][27] real-world varenicline safety among these high-risk population is only explored in few studies, 28 29 several related large observational studies of high-quality were all about general population, rather than specific high-risk population. [30][31][32][33] It is important to further investigate the psychiatric safety of varenicline in special patients with COPD or psychiatric disorder or both in real-world setting to strengthen the knowledge of varenicline safety.…”
Section: Introductionmentioning
confidence: 99%